Relation of serum irisin levels to obesity and non-alcoholic fatty liver disease - Ulualan, Gökçen; Kiraz, Zeynep Küskü; Kırel, Birgül (The Turkish Journal of Pediatrics, 2022)
Background. Irisin is a newly defined myokine which is induced by exercise, which stimulates white fat cells to have the characteristics of brown adipose tissue cell. It thereby causes thermogenesis, energy and weight loss and improvement in insulin sensitivity. These effects of irisin suggest that it may be associated with obesity, insulin resistance and non-alcoholic fatty liver disease (NAFLD). Methods. The aim of the present study was to determine the relationship of serum irisin levels in obese children with NAFLD. A total of 60 pubertal obese adolescents (age range: 11-18 yrs) as well as age and sex matched 28 healthy children were included in the study. Thirty of obese patients had NAFLD. Results. The median irisin levels were lower in the obese patients both with and without NAFLD when compared with the control group. NAFLD group had a higher BMI than obese controls, however, the irisin levels were not different between these groups. The irisin levels were negatively correlated with BMI, BMI SDS, waist, hip and arm circumferences, waist/hip ratio, triceps-biceps skinfold thickness and AST, ALT levels in the all study groups. However, it was positively correlated with BMI, BMI SDS and waist and hip circumference in the entire obese group and positively with BMI SDS in the NAFLD subgroup. Conclusions. Consequently, circulating irisin levels are lower in obese adolescents and negatively correlated with body adiposity. In NAFLD patients, it may be related to steatosis and may decrease with liver damage.
Keywords: children; irisin; non-alcoholic fatty liver disease; obesity